2017
DOI: 10.1111/exd.13249
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNAs in psoriasis: Immunological functions and potential biomarkers

Abstract: MicroRNAs (miRNAs) are small non-coding RNA molecules, which function in RNA silencing and post-transcriptional regulation of gene expression. Psoriasis is an inflammatory skin disease characterized by the dysfunction of keratinocytes, with the immune dysregulation. We reviewed the recent studies on the roles of miRNAs in psoriasis and showed that miRNAs play key roles in psoriasis, including the regulation of hyperproliferation, cytokine and chemokine production in keratinocyte, as well as mediating immune dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 105 publications
(209 reference statements)
2
71
0
1
Order By: Relevance
“…18,19 At present, several biomarkers reflecting severity/activity of psoriasis and response to biologic therapy have been proposed. These biomarkers include genotypes of human leukocyte antigen, cytokine-related genes and inflammation signal-related genes, 20,21 miRNA, 22 serum proteins, 23 such as C-reactive protein, and cytokine-related inflammation and leucine-rich a2-glycoprotein. 24 Among them, neutrophil : lymphocyte ratio can be easily and regularly measured in daily clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 At present, several biomarkers reflecting severity/activity of psoriasis and response to biologic therapy have been proposed. These biomarkers include genotypes of human leukocyte antigen, cytokine-related genes and inflammation signal-related genes, 20,21 miRNA, 22 serum proteins, 23 such as C-reactive protein, and cytokine-related inflammation and leucine-rich a2-glycoprotein. 24 Among them, neutrophil : lymphocyte ratio can be easily and regularly measured in daily clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to long non‐coding RNAs, miRNAs are deregulated in psoriasis skin lesions (s14), reviewed in the article by Liu et al. in Experimental Dermatology . In our initial study, we found a clear separation of psoriasis skin from healthy skin or atopic eczema skin based on miRNA profiles, and identified a tissue‐specific miRNA, miR‐203, with high expression in the skin .…”
mentioning
confidence: 70%
“…Advances in technology have allowed the detection of an increasing number of differentially expressed miRNAs by RNA sequencing, as well as the detection of miRNAs even in archived material (s16, s18). The different methods to analyze miRNA expression are well described and compared in the review article by Liu et al …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A string of differentially expressed microRNAs remains in the focus of psoriasis biology . As reviewed by Liu et al . in the current issue, they are also promising biomarkers.…”
mentioning
confidence: 99%